2010
DOI: 10.4992/jjpsy.80.512
|View full text |Cite
|
Sign up to set email alerts
|

Influence of job-hunting anxiety on job-hunting: From the viewpoint of coping

Abstract: The present study developed a job-hunting anxiety scale and investigated the inuence of job-hunting anxiety on coping, number of job-hunting applications, and satisfaction with job-hunting. Questionnaires were completed by 306 college students who had started job-hunting. Explorative factor analysis extracted ve factors such as "appeal anxiety" , "support anxiety" , "activity persistence anxiety" , "test anxiety" , and "a lack of readiness anxiety" . Analysis of covariance structures indicated that a job-hun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Although our model was not supported, our results suggest that a cognitive/thinking style of acceptance and positive reframing of stressful events, finding meaning in life, and optimism about the future (i.e., S-P) may reduce people to anxiety in job hunting and promote career exploration. Moreover, the negative association between career choice anxiety and career exploration is evidence that supports previous studies that have addressed anxiety as a psychological problem in job hunting and have shown a negative association with maladjustments in job hunting, such as job hunting activities [1] and career decisions [16].…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Although our model was not supported, our results suggest that a cognitive/thinking style of acceptance and positive reframing of stressful events, finding meaning in life, and optimism about the future (i.e., S-P) may reduce people to anxiety in job hunting and promote career exploration. Moreover, the negative association between career choice anxiety and career exploration is evidence that supports previous studies that have addressed anxiety as a psychological problem in job hunting and have shown a negative association with maladjustments in job hunting, such as job hunting activities [1] and career decisions [16].…”
Section: Discussionsupporting
confidence: 85%
“…All scores indicated that higher composite scores indicated greater subjective childhood SES, S-P, career choice anxiety, and career exploration. Before conducting the moderated mediation analysis, the following steps were performed (cf., [15]): (1) The direct effect of SES on career exploration and the indirect effects via career choice anxiety were examined by performing the mediation analysis; (2) Through the moderation analysis was examined whether S-P can buffer the association between SES and career choice anxiety, and between SES and career exploration. In addition, 95% confidence intervals were reported in this analysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations